2017
DOI: 10.1007/s12220-016-9756-1
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Estimation of a Potential and Cone Conditions of a Body

Abstract: We investigate a potential obtained as the convolution of a radially symmetric function and the characteristic function of a body (the closure of a bonded open set) with exterior cones. In order to restrict the location of a maximizer of the potential into a smaller closed region contained in the interior of the body, we give an estimate of the potential using the exterior cones of the body. Moreover, we apply the result to the Poisson integral for the upper half space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In [21], it was shown that if h ≥ √ m + 2 diam Ω, then Ω has a unique illuminating center, and that, as h goes to infinity, the unique illuminating center converges to the centroid of Ω. In [23], it was shown that the limit point of any convergent sequence of illuminating centers c(h j ) of height h j with h j → 0 + is an r −1−m -center. Thus an illuminating center moves with respect to h in general.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], it was shown that if h ≥ √ m + 2 diam Ω, then Ω has a unique illuminating center, and that, as h goes to infinity, the unique illuminating center converges to the centroid of Ω. In [23], it was shown that the limit point of any convergent sequence of illuminating centers c(h j ) of height h j with h j → 0 + is an r −1−m -center. Thus an illuminating center moves with respect to h in general.…”
Section: Introductionmentioning
confidence: 99%